1979
DOI: 10.1021/bi00575a004
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical analysis of membrane vesicles from Escherichia coli

Abstract: Membrane vesicles isolated from Escherichia coli ML 308--225 have been analyzed by crossed immunoelectrophoresis, and immunoprecipitates corresponding to the following cellular components have been identified: ATPase (EC 3.6.1,3), two or three NADH dehydrogenases (EC 1.6.99.3), D-lactate dehydrogenase (EC 1.1.1.27), glutamate dehydrogenase (EC 1.4.1.4), dihydro-orotate dehydrogenase (EC 1.3.3.1), 6-phosphogluconate dehydrogenase (EC 1.1.1.43), polynucleotide phosphorylase (EC 2.3.7.8), beta-galactosidase (EC 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…As indicated, a perplexing problem was the continued acylation (even after addition of ample cold penicillin), before deacylation of some of the PBPs in only the osmotically fragile (3% [wt/vol] NaCl) membranes. It was suggested that membranes obtained by use of the X-press may lead to predominately "inside-out" (i.e., inverted) membrane vesicles, as opposed to sonication, which results in scrambled vesicles (11)(12)(13)16). Under these conditions, the possibility remained that cold penicillin might be greatly retarded in its penetration of these inside-out vesicles to terminate binding of labeled antibiotic (Dougherty, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…As indicated, a perplexing problem was the continued acylation (even after addition of ample cold penicillin), before deacylation of some of the PBPs in only the osmotically fragile (3% [wt/vol] NaCl) membranes. It was suggested that membranes obtained by use of the X-press may lead to predominately "inside-out" (i.e., inverted) membrane vesicles, as opposed to sonication, which results in scrambled vesicles (11)(12)(13)16). Under these conditions, the possibility remained that cold penicillin might be greatly retarded in its penetration of these inside-out vesicles to terminate binding of labeled antibiotic (Dougherty, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…The E. coli NDH-2A was further characterized and showed to contain 1 mol of noncovalently bound FAD per mol of purified enzyme; moreover, it consists of a single polypeptide with M r 47,200, which in the mature form has an apparent molecular mass of 45 kDa (30). The NDH-2A from the E. coli respiratory chain faces the cytosol (62).…”
Section: Biochemical and Genomic Aspects Of Nad(p)h Dehydrogenasesmentioning
confidence: 99%
“…Cytoplasmic membrane vesicles from Escherichia coli that have the same (right-side-out; refs. [6][7][8][9][10][11] or the opposite (inverted; refs. 12-15) orientation as the membrane in the intact cell retain the capacity to convert respiratory energy into a IATH+, and studies with these preparations have provided virtually unequivocal support for the central obligatory role ofchemosmotic phenomena in active transport (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…pBR322 DNA (10 Ag) was linearized in 300 Al of 20 mM Tris HCl, pH 7.0/100 mM NaCl/7 mM MgCl2/2 mM 2-mer--captoethanol containing 10 units of BamHI at 37"C for 15 …”
mentioning
confidence: 99%